Preparation and Characterization of Adsorbents from Kluwak Shell (Pangium edule) Modified by Surfactant of HDTMA-Br - Ananda, Zhafira Dwika; Dewi, Ratna Sari (Journal of The Indonesian Society of Integrated Chemistry, 2024)
This research aims to determine the characteristics of adsorbents made from kluwak shell activated carbon modified by HDTMA-Br surfactant. Providing adsorbents is carried out using the contacting method. The FTIR characterization results show the presence of the CH3 from N-(  group possessed by the HDTMA-Br surfactant at wave number 1500 . SEM characterization shows that the morphology of HDTMA-Br surfactant modified active carbon appears to have a surface with some of the pores closed due to electrostatic interactions compared to unmodified active carbon which has open pores. The results showed that the functional groups and morphology of activated carbon changed after contact with HDTMA-Br surfactant which was related to the absorption capacity of activated carbon.